(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
There are many techniques can be adopted for improving power system performance. This is because the difference between generated and required powers. In general, this difference causes frequency deviation in all electrical network. Therefore, most of the scientists invented some techniques which help in controlling frequency of electrical models. Changing speed regulation method and applying PID controller are some these techniques. Therefore, this paper highlights these two mechanisms. First technique is speed regulation which will be changed in four values. These values are lower, equal, and higher than critical speed regulation (Rcr). Speed regulation changes tested model from unstable situation to stable with suitable response. However, steady state frequency deviation and power losses remain continuously. Therefore, second technique is added. It is applying PID controller. Similarly, the gains PID controller are varied three times. Practical characteristics of the model are demonstrated. They show a clear enhancing in different features such as rising time, settling time, peak time, and peak value. PID controller helps largely in melting continuous frequency drop and power losses gradually. In fact, the model of suggested system is designed by MATLAB program. In brief, speed regulation, PID controller are main techniques in keeping frequency of power systems in normal values. This supports efficiently in avoiding numerous electrical disturbances.